2017
DOI: 10.1186/s12895-017-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of the medical personnel regarding atopic dermatitis in Yaoundé, Cameroon

Abstract: BackgroundAtopic dermatitis (AD) is a chronic, relapsing and pruritic inflammatory skin disease whose management remains unclear to most non-dermatologists. This study aimed to assess the knowledge, attitudes and practices (KAP) of the medical staff regarding AD in Yaoundé, Cameroon.MethodsThis was a cross-sectional study conducted from January to April 2014 in 20 health facilities located in Yaoundé, the capital city of Cameroon. All medical staff who provided their consent were included in the study. A score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
5
2
Order By: Relevance
“…A study by Kouotou et al assessed the knowledge, attitudes, and practices of medical personnel regarding atopic dermatitis. Twenty-two percent of the participants were nurses, and 45% of them showed a moderate level of knowledge, with none in the good level of knowledge category [20]. Although we attempted to study knowledge on dermatology and not a specific disease, our study's findings agree with the findings of the above research, as most of our study participants were also in the low to moderate knowledge category and none were in the good knowledge category.…”
Section: Discussionsupporting
confidence: 85%
“…A study by Kouotou et al assessed the knowledge, attitudes, and practices of medical personnel regarding atopic dermatitis. Twenty-two percent of the participants were nurses, and 45% of them showed a moderate level of knowledge, with none in the good level of knowledge category [20]. Although we attempted to study knowledge on dermatology and not a specific disease, our study's findings agree with the findings of the above research, as most of our study participants were also in the low to moderate knowledge category and none were in the good knowledge category.…”
Section: Discussionsupporting
confidence: 85%
“…The findings revealed that the community had poor attitude towards skin diseases similar to a study carried out in Yaounde, Cameroon which reported poor attitude among the general practioners while 60% of the study participants had poor attitude towards Atopic dermatitis. 7 The findings are contrary to a study carried out in Pesantren Darul Fwata which reported 80% good attitude towards scabies among the Santri. 8 In addition, the findings indicated that majority of the community members would be embarrassed due to skin diseases similar to a study in Kaduna, Nigeria where the participants reported to be ashamed, embarrassed and were uncomfortable of their skin condition due to Pityriasis versicolor, and a study among adults in Malaysian city which reported that 77.1% of the adults would be embarrassed due to skin infection.…”
Section: Community Perception Towards Skin Diseasescontrasting
confidence: 78%
“…The findings revealed generally poor practice towards prevention of skin diseases among the community members similar to a study in Cameroon which reported poor practice among medical personnel on the prevention of atopic dermatitis. 7 In addition, the study recorded poor practice towards prevention of T. capitis and P. versicolor contrary to a study among the Santri which reported 60% moderate practice towards scabies among the Santri. 8 However, the study revealed good practice towards prevention of T. corporis similar to a study among the nursing students were 81.1% of the study participants' recorded good practice; and in addition, majority of the community members avoided sharing of personal belongings as a prevention measure towards skin diseases similar to which reported 100% of the nursing students supported that individuals should not share clothes with friends, never sleep in others bed and never borrow clothes from other people.…”
Section: Community Perception Towards Skin Diseasescontrasting
confidence: 60%
“…The worldwide prevalence of AD ranges from 15% to 20% in children and from 1% to 3% in adults; it is 3% in sub-Saharan Africa [1,[5][6][7]15]. In Cameroon, Kouotou et al found a prevalence of 14.8% in the general population [16,17]. Being on the rise worldwide, including in low-income countries, AD represents a real public health problem [1,3,8,9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Being on the rise worldwide, including in low-income countries, AD represents a real public health problem [1,3,8,9,18,19]. In addition, there are difficulties in its diagnosis and management due to the inappropriate level of knowledge of the nursing staff, problems in acceptance by patients and difficulties in accessing treatment [2,[7][8][9]16,[20][21][22][23]. In addition, it has a major socio-economic impact on the lives of patients due to the cost of treatment, stigmatization, sleep disorders, and the inconvenience in professional and personal activities (impaired quality of life in 93.5% of individuals affected in Cameroon) [1,15,21,24].…”
Section: Introductionmentioning
confidence: 99%